2017
DOI: 10.1371/journal.pone.0169000
|View full text |Cite
|
Sign up to set email alerts
|

Thirty-Year-Old Paradigm about Unpalatable Perch Egg Strands Disclaimed by the Freshwater Top-Predator, the European Catfish (Silurus glanis)

Abstract: So far, perch egg strands have been considered unpalatable biological material. However, we repeatedly found egg strands of European perch (Perca fluviatilis) in the diet of European catfish (Silurus glanis) caught by longlines in Milada and Most Lakes, Czech Republic. The finding proves that perch egg strands compose a standard food source for this large freshwater predatory fish. It extends the present knowledge on catfish foraging plasticity, showing it as an even more opportunistic feeder. Utilization of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 28 publications
0
23
0
Order By: Relevance
“…However, more studies are therefore needed in this direction to confirm these findings and to increase information on these alien species' impacts. These future sampling campaigns should also consider summer and autumn because behaviors and thus, interactions may differ (Vejrík et al, 2017a), potentially further enhancing our comprehension of mechanisms underlying biological invasions and species interactions.…”
Section: A Case Study On Alien Species Communities?mentioning
confidence: 99%
“…However, more studies are therefore needed in this direction to confirm these findings and to increase information on these alien species' impacts. These future sampling campaigns should also consider summer and autumn because behaviors and thus, interactions may differ (Vejrík et al, 2017a), potentially further enhancing our comprehension of mechanisms underlying biological invasions and species interactions.…”
Section: A Case Study On Alien Species Communities?mentioning
confidence: 99%
“…Previous studies showed that increased fish catch can be positively correlated with increased fish abundance in the ecosystem (Mosindy & Duffy, ; Skov et al, ). Since catfish predation can potentially have a significantly negative effect on freshwater fish populations (Vejřík, Vejříková, Blabolil, et al, ; Vejřík, Vejříková, Kočvara, et al, ), it is possible that catfish will become a new source of conflict between fisheries and environmental protection in Central Europe (similarly to Eurasian otter Lutra lutra and great cormorant Phalacrocorax carbo ) (e.g., Kortan & Adámek, ; Lyach, Blabolil, & Čech, ; Lyach & Čech, , ). Higher population densities of catfish could potentially lead to population decrease in prey fish species (mostly cyprinids) and therefore to decreased harvest of cyprinids.…”
Section: Discussionmentioning
confidence: 99%
“…data). Majority of rivers in the study area have naturally reproducing populations of catfish (Vejřík, Vejříková, Blabolil, et al, ; Vejřík, Vejříková, Kočvara, et al, ). Eurasian catfish is a native fish species in the study area.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations